Tumor Microenvironment in Colorectal Cancer Development: A Review of 3D Study Analysis - Angka, Rebecca Noerjani; Sudoyo, Aru Wisaksono; Siregar, Nurjati Chairani; Jeo, Wifanto Saditya; Antarianto, Radiana Dhewayani (http://dharmais.co.id/, 2024)
Background: Colorectal cancer is the third most common cancer in 2020, with a high mortality rate. Colorectal cancer treatment has made many advances. However, many factors in the tumor microenvironment still have not been reached but significantly affect the success of treatment. This literature review was conducted to search for research articles that analyze factors in the tumor microenvironment, how they interact through studies primarily conducted in 3D, and how to prepare for 3D research on colorectal cancer will be briefly discussed. The aim of this systematic review is to study the components of the tumor microenvironment in colorectal cancer development as assessed by 3D studies. Methods: Article searches were conducted through Embase, Scopus and PubMed. From the 110 articles found at the beginning of the search, after going through several screening stages, 27 articles were determined that met the inclusion criteria. The inclusion criteria used were journals containing research articles on colorectal cancer in the last five years with topics regarding the tumor microenvironment and according to keywords. Results: Microenvironment components in colorectal cancer, consisting of cellular and noncellular components, have the most significant effect on cancer development and ultimately affect metastasis, response to treatment, and prognosis. Conclusions: This literature review proves that the components of the tumor microenvironment are very diverse, making colorectal cancer heterogeneous. It still requires a lot of research to prove the existence of other components that affect the effectiveness of the treatment.